2009
DOI: 10.1590/s1678-77572009000600005
|View full text |Cite
|
Sign up to set email alerts
|

A survey of cross-infection control procedures: knowledge and attitudes of Turkish dentists

Abstract: Objectives:The objective of this study was to investigate the knowledge, attitudes and behavior of Turkish dentists in Samsun City regarding cross-infection control.Material and methods:A questionnaire was designed to obtain information about procedures used for the prevention of cross-infection in dental practices and determine the attitudes and perceptions of respondent dental practitioners to their procedures. The study population included all dentists in the city of Samsun, Turkey, in April 2005 (n=184). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 23 publications
(22 reference statements)
5
60
2
5
Order By: Relevance
“…Yuzbasioglu et al [7] study (2009) showed that improved compliance with recommended infection control procedures is required for all dentists and continuing education programs and short-time courses about cross-infection and infection control procedures are suitable to improve the knowledge of them [7].…”
Section: Discussionmentioning
confidence: 99%
“…Yuzbasioglu et al [7] study (2009) showed that improved compliance with recommended infection control procedures is required for all dentists and continuing education programs and short-time courses about cross-infection and infection control procedures are suitable to improve the knowledge of them [7].…”
Section: Discussionmentioning
confidence: 99%
“…A study among Turkish dentists found poor knowledge about control of cross infection. [18] The difference existed between self-reported knowledge and practice of the dentists' regarding disposal of waste in different color-coded bags. On one hand, majority of dentists reported that they were aware of BMW disposal system and about the color-coding followed for waste disposal, but actually on the other hand, they were not practicing waste disposal in the appropriate color-coded bags.…”
Section: Methodsmentioning
confidence: 99%
“…7 DiĢ hekimliğinde enfeksiyon kontrolünün sağlıklı bir Ģekilde gerçekleĢtirilebilmesi amacıyla enfeksiyon kontrolünün en önemli aĢaması olan sterilizasyon ve dezenfeksiyon kurallarının iyi bilinmesi ve uygulanması gerekmektedir.…”
Section: (Tablo 1)unclassified